Survey of lines in M 31: [CII] as SFR tracer at 50 pc scales. Issue Volume 10:Issue S309(2014) (9th February 2015) - Kapala, M. J.; Sandstrom, K.; Groves, B.
Abstract : The [CII] 158 μm line is typically the brightest far-IR emission line from star-forming galaxies. As such, this line is a possible tracer of star-formation, but to do so we need the relative contributions of different ISM phases. Using high physical resolution observations of the [CII] 158 μm line from Herschel PACS in five 3'×3' field in M 31 and optical IFU spectra from PPaK and ancillary IR data, we are able to spatially separate out the ISM phases Kapala . We find that a large fraction of [CII] emission in M 31 arises from diffuse gas ( 20–90), with a sub-linear relation of [CII]–SFR at 50 pc scales. However, on kpc scales, the observed empirical [CII]–SFR relation is in agreement with other extragalactic studies.